การทบทวนร่างแผนยุทธศาสตร์การคุ้มครองผู้บริโภคแห่งชาติ พ.ศ. 2560 - 2564 - ลีลากิจไพศาล ยุทธพงษ์ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
This study aims to 1) review the former Consumer Protection Strategic Plan 2012 and make amendments to ensure its suitability with the current circumstances; 2) make the draft of Consumer Protection Strategic Plan 2016 – 2020; and 3) put the Consumer Protection Strategic Plan 2016 - 2020 into practice by implementing a qualitative research approach. A purposive sampling was used to select participants from the Office of the Consumer Protection Board and 21 relevant government agencies. Brainstorming, in-depth interview, and workshop were employed for data collection. The first research result revealed that the draft of the new Consumer Protection Strategic Plan was in accordance with the others relevant government plan and its objective is to integrate all consumer protection units to protect consumers with fairness, equilibrium, and sustainability. Regarding the second research objective, it was found the types of operation could be classified into 4 categories: (1) providing knowledge and information (2) inspecting and monitoring (3) reviewing complaints from consumers, and (4) developing laws relating to consumer protection. As for the approaches to enhance the efficiency of the plan is to develop the integration system and other relevant consumer protection mechanisms. The example for KPIs were (1) the number of products and services tested for quality and safety, (2) the consumer complaint and problem database to record consumers’ problems, (3) the number of publicized activities, body of knowledge or content relating to consumer protection in various issues, (4) the percentage of the members with required knowledge, and (5) the operational achievements as stated in the action plan.